Ancient Turkic Inscriptions - Turdibekov Mominjon Turaevich (International Journal on Orange Technologies, 2021)
Appearance of writing, it‟s influence on the development of society, saving stories for eternity and transferring them to long distances, the writings used by ancient Turkic peoples - these are themes considered in this article